GHARAR AND TADLIS IN INFORMAL FUEL SUPPLY CHAINS: A COMPILATION OF SHARIA ECONOMIC LAW ANALYSIS OF COLLECTOR AND RETAIL GASOLINE TRANSACTIONS IN BANJAR KEJEN VILLAGE - Zaenal Abidin; Dewi Masita (IZZI: Jurnal Ekonomi Islam, 2025)
This study examines a prevalent yet analytically neglected informal economic phenomenon through the lens of Sharia law: the retail gasoline trading system embedded within non-formal rural supply chains. Informal fuel distribution constitutes a critical dimension of rural economic life in developing Muslim-majority economies, yet it has received minimal systematic normative examination. The research novelty lies in its systematic application of the Compilation of Sharia Economic Law (Kompilasi Hukum Ekonomi Syariah / KHES) as a structured analytical instrument rather than merely a normative backdrop for diagnosing contract validity, gharar, tadlis, and ihtikar within village-level informal fuel distribution mechanisms. Prior scholarship has addressed retail fuel practices primarily from macro-economic and general regulatory perspectives leaving a significant gap in micro-transactional Sharia analysis. Employing a descriptive qualitative case study design through direct observation, in-depth semi-structured interviews, and documentation in Banjar Kejen Village, Pandaan District, Pasuruan Regency, East Java, Indonesia, the research identifies four interrelated normative deficiencies: (1) transactions proceed without explicit ijab-qabul (offer and acceptance) or written contracts, violating KHES (2) systematic volume discrepancies  caused by the collector transporting fuel in a motorcycle tank, consuming a portion en route  constitute gharar fahish (serious uncertainty) in the object of exchange; (3) the collector's non-disclosure of this volume deficit constitutes tadlis (concealment of material fact), regardless of fraudulent intent; and (4) the single-collector monopoly structure creates the structural conditions for ihtikar (market cornering), warranting preventive regulatory attention.The study argues that the appropriate policy response is not elimination but Shariah-ification (syariahisasi) of the existing system through formalized contracts, transparent measurement protocols, and muamalah education for informal rural business actors. It contributes a holistic, operationally grounded analytical framework that previous single-dimension studies have not provided.